Geographical analysis of rural-urban disparities in housing conditions in Haryana: A spatial perspective - Ritu Rani; Sandeep; Rajesh Kumar; Salesh Kalkal (National Geographical Journal of India, 2024)
Food and shelter are fundamental needs of human beings. The condition of housing in any geographical region represents the fundamental shelter needs of human beings. A robust database exists in India in the form of census, which if utilized appropriately, can reveal extensive as well as in-depth information about the housing conditions across the states. The quality of dwelling units of a society reflects the overall level of achievement of a society or a section thereof. Hence it can serve as a meaningful and valid parameter of the level of socio-economic development of a certain geographical region or a section of the population. As is the case with other amenities, there exists a wide gap in rural and urban areas in terms of housing conditions. Most comprehensive data in this regard is collected by the census of India once every ten years. Hence the present study is an attempt to conduct a rigorous spatial analysis utilizing the household-level quantitative database, so as to bring out the disparities in rural and urban areas of Haryana, before presenting the key findings employing suitable geographical tools.